(untitled) (Bangladesh Journal of Agricultural Research, 2016)
A pot experiment was conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during kharif season of 2010 to investigate the genetic divergence of some mungbean genotypes under nutrient stress condition using Mahalanobis statistic (D2) and principal component analysis. Analysis of variance showed significant difference for all the characters. Results of multivariate analysis revealed that 200 mungbean genotypes formed five clusters at nutrient stress condition where cluster II had the maximum genotypes (83) followed by cluster I (65), cluster III (30), cluster IV (9) and then cluster V (13). The highest intra-cluster distance was observed between cluster IV containing lowest 9 genotype and cluster V containing 13 genotypes. The highest inter-cluster distance was observed between cluster IV and III and lowest was observed between cluster V and Cluster I. Cluster III had the highest cluster mean for total dry matter, root dry mass, pods per plant, seeds per pod, 1000 seed weight and seed yield. Considering cluster distance and other agronomic performance the genotypes IPSA 1, IPSA 12, IPSA 5 and others genotypes from cluster III may be considered for better performance under nutrient stress condition. Bangladesh J. Agril. Res. 41(2): 377-386, June 2016